Redefining Customer Experience in the COVID-19 Pandemic: Empirical Approach of Home Furnishings Retailer - Daniel Hermawan (Cita Konsultindo Research Center, 2022)
One of the most important factors in succeeding in the commercial rivalry is customer experience. The Covid-19 pandemic, which was accompanied by a health and financial catastrophe, has altered the way that customers interact with brands. This study aims to map out strategic concerns that are the main factors in improving and identify customer experiences that happened during the Covid-19 pandemic. Data were gathered for the study utilizing qualitative methodologies, including interviewing and employing tools for observation. With the aid of a phenomenological qualitative design model, the data were processed and examined. The findings of this study demonstrate that regulations in the implementation of health protocols, such as the employment of a queue system, the use of masks, and restrictions on enjoying props, also alter how customers enjoy the customer experience. To bridge the gap between customers' desire to enjoy an activity and their awareness of health dangers, businesses must introduce new mechanisms into the customer experience during the Covid-19 pandemic. According to the study's findings, personal experience, social media, and constraints all have an impact on how customers experience the Covid-19 pandemic.